El referente de la internacionalización y sus inherencias para la educación superior pública - Muñoz Varela, Luis (2012)
This article approaches the subject of internationalization as a dimension of programs and politics in higher education. For the purposes of this study, an extensive bibliography on the results of previous research studies was reviewed. The studies deal with this dimension of political and academic processes. The studies were carried out in the recent years in institutions and systems of higher education in different regions and countries of the world. As point of departure, the article discusses the implications that the society of knowledge and globalization have on higher education. It also identifies the academic and the institutional scopes in which the dimension of internationalization has been more meaningful as a result of its incorporation in politics and in the programmatic endeavors of institutions of higher learning.